The Brazilian soil total available water (TAW) acquired by remote sensing and machine learning techniques - Letícia Guadagnin Vogel; Fellipe Alcantara de Oliveira Mello; José Alexandre Melo Demattê; Quirijn de Jong van Lier; Jorge Tadeu Fim Rosas; Leonardo Inforsato; Merilyn Taynara Accorsi Amorim; Nícolas Augusto Rosin; Michele Duarte de Menezes; Marcelo Henrique Procópio Pelegrino; Danilo Cesar de Mello; Renan Falcioni (CATENA, 2026)

Venom characterization and structural insights into phospholipase D isoforms from the spider Loxosceles aff. variegata - Ana Luiza Silva-Araújo; Rafaela Silva-Magalhães; Pamella Peres-Damásio; Elaine Henriques Teixeira Pereira; Ramon de Oliveira Souza; Luana Silveira da Rocha Nowicki Varela; Luiz Marcelo Ribeiro Tomé; Felipe Campos de Melo Iani; Adriano Lima Silveira; Márcia Helena Borges; Raíssa Medina-Santos; Carlos Chavez-Olórtegui; et al. (Toxicon, 2026)

Effects of waterlogging on pollutant availability in iron mining tailings and the tolerance response of Typha domingensis Pers - Marcelo Ramos de Anchieta; Kauê Shindi Dias Nakamura; Amanda Coletti Santolino; Carlos Henrique Goulart dos Reis; Vitor Hugo Silva Ribeiro; Vinícius Politi Duarte; Fabricio José Pereira (Environmental Science and Pollution Research, 2026)
Soil flooding can increase nutrient and pollutant availability to plants; however, the effects in iron mining tailings are still unclear. This work hypothesizes that waterlogging increases the availability of elements present in iron mining tailings, but tolerant aquatic plants can survive under these conditions, showing potential for phytoremediation. This work investigated how flooding affects the availability of essential elements and metal pollutants in iron mining tailings and how this affects the growth, root anatomy, and pollutant content in the aquatic plant Typha domingensis (cattail). Cattail clones were grown in pots containing iron mining tailings under two irrigation conditions: field capacity and waterlogged. The experimental design was completely randomized with 18 replicates and two treatments ( n = 36), and the experiment was conducted for 180 days. The pH, electrical conductivity, and total dissolved solids were measured from the iron mining tailings and the plant contents of Al, Cd, Cr, Pb, Fe, and Ca, as well as their growth and root anatomy were evaluated. Waterlogging increased the pH (from 6 to 7), total dissolved solids (from 61.9 to 140.8 ppm), and the electrical conductivity (from 113.2 to 282.1 µs cm −1 ) of iron mining tailings, suggesting higher ion availability in the water. Waterlogging of iron mining tailings also increased the elemental uptake, ranging from 50 to 178% depending on the element considered. No growth limitation was observed since waterlogging also increased the root dry and fresh masses, the root:shoot ratio, the root biomass allocation, and plant dry mass from cattail. Waterlogging of iron mining tailings also increased the root cortex area, the exodermis thickness, and the vascular cylinder area. Results suggest that waterlogging of iron mining tailings increases the availability and uptake of elements by T. domingensis , which, nevertheless, suffers no significant growth limitations and shows relevant potential for the remediation of iron mining tailings when the pollutant is present in natural wetlands and when the species is used in remediation systems.

Biomarkers of acute kidney injury in crotaline envenomation in the Brazilian Amazon - Renato do Carmo Said; Vera Lúcia Teixeira de Freitas; João Guilherme Pontes Lima Assy; Olivia Campos Pinheiro Berreta; Alisson dos Santos Brandão; Isadora Calderaro Soares; Marcelo Ribeiro Duarte; Lia Junqueira Marçal; Emmanuel A. Burdmann; Francisco Oscar de Siqueira França (Toxicon, 2026)

Regional patterns of environmental variability in mangrove ecosystems along the southeastern Brazilian coast - Marcelo Antonio Amaro Pinheiro; Luis Felipe de Almeida Duarte; Caio Rodrigues Nobre; Esli Emanoel Domingues Mosna; Rodrigo dos Santos Rodriguez-Lopes; Todor Petkov; Aleksandar Dimitrov; Dimitrinka Ivanova (Regional Studies in Marine Science, 2026)

Association of Nepeta cataria L. essential oil and eugenol: synergism and safe anesthesia in tambaqui Colossoma macropomum (Cuvier, 1818) - Taissa Viana Damasceno; Thaysa de Sousa Reis; Axell Lins; Priscille Fidelis Hartcopff; Marcelo Victor dos Santos Brito; Daniella Rocha Bittencourt; Luiz Fernando Duarte de Andrade Junior; Alicia Chaves Manito; Gabriela de Paula Goyana; Cibely Camille Fernandes Ferreira; Dayanne Raquel de Sousa Barros; Luana Vasconcelos de Souza; et al. (Veterinary Research Communications, 2026)
Anesthetics are widely employed in aquaculture and in research environments utilizing fish as experimental models, with the aim of mitigating stress and hypermotility during handling procedures. Among the most commonly used anesthetic agents, eugenol stands out for its suitability across multiple species, enabling safer handling and transportation while minimizing physiological impact on the animals. For the experimental procedure, three oil mixtures were prepared in a 1:1 ratio. The first contained 50% eugenol and 50% Nepeta cataria essential oil (ENCO); the second mixture was 50% eugenol and 50% corn oil ( Zea mays ) (ECO); and the third was 50% Nepeta cataria essential oil and 50% corn oil (NCCO). The present study proposes a behavioral and electrophysiological assessment of Colossoma macropomum subjected to immersion baths containing different concentrations of Nepeta cataria L. 50% and eugenol 50%, in addition to investigating the underlying components of the synergism and the mechanism of action of eugenol. A total of 288 juvenile specimens, of mixed sex, with a mean body mass of 25.34 ± 3.2 g, were used. Experiment 1: assessed the synergistic potentiation between the compounds, based on latency times for anesthetic induction and recovery. Experiment 2: performed electrophysiological analyses of muscle (EMG) and cardiac (ECG) functions. Experiment 3: evaluated the influence of flumazenil on the activation of the anesthetic agents. Evaluations were conducted during 10-minute immersion baths at concentrations of 30 µL·L⁻¹, 35 µL·L⁻¹, 40 µL·L⁻¹, 45 µL·L⁻¹, and 50 µL·L⁻¹. The combination of Nepeta cataria essential oil and eugenol promotes good muscle relaxation and minor alterations in the cardiovascular system, promoting easily reversible bradycardia. The findings indicate that the combination of Nepeta cataria essential oil and eugenol constitutes a promising and safe alternative, due to the synergistic reduction in induction time and the maintenance of cardiac safety, which allowed for a reduction in the concentration required without compromising the maintenance of the anesthetic plane. Furthermore, flumazenil was found to exert a significant influence on both the induction process and the recovery phase of anesthesia.

Potential of the bivalve Perna perna as bioindicator of eutrophication in tropical coastal ecosystems: carbon and nitrogen stable isotopes, fatty acids and shell morphometry - Thaís Erbas; Tarik Meziane; Aguinaldo Nepomuceno; Edson Pereira; Michele Duarte; Nilva Brandini; Mauricio Cerda; Pierre Le Moal; Lorena S. Nascimento; Marcele Abreu; Wilson Machado; Marcelo Bernardes; et al. (Marine Environmental Research, 2026)

Topology optimization using the Material Field Series Expansion method and the Covariance Matrix Adaptation-Evolution Strategy: A potential tool for crashworthiness applications - Marcelo Rubens Galdiano Duarte; Pablo Andrés Muñoz-Rojas; Fabian Duddeck; Marcílio Alves (Engineering Structures, 2026)

Oil-based oleogels from yeast Yarrowia lipolytica NRRL Y-1095: Enhancing nutritional, rheological and oxidative stability properties - Bruno Roswag Machado; Marcelo Gomes Soares; Rosiane Lopes Cunha; Susan Hartwig Duarte; Lucielen Oliveira Santos (Food Structure, 2026)

UV radiation decreases photosynthesis in Typha domingensis, but the species shows tolerance mechanisms related to anthocyanin production and clonal growth - Carlos Henrique Goulart dos Reis; Marcelo Ramos de Anchieta; Amanda Coletti Santolino; Kauê Shindi Dias Nakamura; Murillo Tinheira do Prado; Vitor Hugo Silva Ribeiro; Vinícius Politi Duarte; Evaristo Mauro de Castro; Fabricio José Pereira (Flora, 2026)

Record of Stiff-legged Defensive Behavior in Rhinella achavali (Anura: Bufonidae) - Michele Esperança; Camila Fernanda Moser; Gustavo Kasper Cubas; Samuel Ferreira Gohlke; Marcelo Duarte Freire; Márcio Borges-Martins (acta ethologica, 2026)

Industrial-scale fermentation of Arara coffee in A 15,000 L bioreactor: Impacts of process variables on quality and sensory profiles - Laila Alonso; Gisele Xavier Ribeiro Costa; Karolina Prisco Borba; Luiza Manuela Alves Braga Cardoso; Marcelo Antônio Duarte da Cruz; Christiano Vieira Pires; Pedro Luiz Lima Bertarini; Matheus de Souza Gomes; Laurence Rodrigues Amaral; Renata Abadia Reis Rocha; Liliane Maciel de Oliveira; Líbia Diniz Santos (Food Research International, 2026)

Kernel processing and storage length: Effect on the fermentation, nutritional, and physical characteristics of flint corn silage with low DM - Marina Elizabeth Barbosa Andrade; Juliana Duarte Messana; Marcelo Gindri; Jéssica Rocha Sousa Gervásio; Matheus Mello Silva; Carlos Henrique Silveira Rabêlo; Ricardo Andrade Reis (Animal Feed Science and Technology, 2026)

Zinc and circulating microRNAs in women with insulin resistance - Danielle Caroline da Silva Dias; Graziela Biude Silva Duarte; Leonam da Silva Pereira Batista; Marcelo Macedo Rogero; Fernando Barbosa; Silvia Maria Franciscato Cozzolino; Raquel Costa Silva Dantas-Komatsu; Karina Zaira Silva Marinho Costa; Bruna Zavarize Reis (Journal of Trace Elements in Medicine and Biology, 2025)

Quantitative summary of nine years of fungicide efficacy data for managing white spot and protecting yield in maize - MonalisaC. De Cól; Karla Braga; AdrianoA.P. Custódio; Marcelo G. Canteri; Lucas H. Fantin; Carlos M. Utiamada; Hércules D. Campos; Dagma D. Silva-Araújo; Rodrigo V. Costa; InêsF.U. Yada; Aildson P. Duarte; Alfredo R. Dias; et al. (Crop Protection, 2025)

Ohmic heating for attenuation of Lactobacillus acidophilus LA-5 in Minas Frescal cheese: probiotic survival, biological activity, and in vitro antimicrobial activity - Cássia P. Barros; Tatiana C. Pimentel; Ramon Silva; Maria Carmela K.H. Duarte; Eliane T. Mársico; Erick A. Esmerino; Pedro Henrique C. Felix; Carlos Augusto F. Oliveira; Beatriz L. Valente; Marcelo Cristianini; Mônica Q. Freitas; Adriano G. Cruz (Food Research International, 2025)

Corrigendum to “Evaluation of the toxic and genotoxic effects of exposure of Drosophila melanogaster to the glutathione-capped AgIn5Se8@ZnS nanocrystals” [Chemosphere, (2025), vol. 381, pages 144482] - Antônio Marcos de Oliveira dos Santos; Danilo Gustavo Rodrigues Silva; Maria Gislaine Pereira; Adrielle Rodrigues Costa; Claudia Rohde; Camila Caroline Lopes Arruda; Antônia Eliene Duarte; Lizandra Ferraz da Silva; Denilson Vasconcelos Freitas; Marcelo Navarro; Maríndia Deprá; Daniela Maria do Amaral Ferraz Navarro; et al. (Chemosphere, 2025)

In vitro antihypertensive effects of Viscum album mother tinctures in kidney proximal tubule cells - Rodrigo dos Santos Pinto Duarte; Michelle Nonato de Oliveira Melo; João V.C. Batista; Giovanna Gomes Martins; Adriana Passos Oliveira; Rosilane Taveira da Silva; Marcelo Einicker Lamas; Stephan Baumgartner; Carla Holandino (Phytochemistry Letters, 2025)

Mineralogical insights into the potentially toxic elements and health risks in lacustrine environments in the Lower Doce River, Southeastern Brazil - David Lukas de Arruda; Luiz Aníbal da Silva Filho; Sara Ramos dos Santos; Gilberto Fonseca Barroso; Marcelo Metri Corrêa; Paulo Jorge Sanches Barbeira; Danniel Brandão Mendes; Vânya Márcia Duarte Pasa; Danilo de Lima Camêlo (Environmental Geochemistry and Health, 2025)

Ontogenic, Immunological, and Behavioral Changes of Crack Cocaine Exposure During the Gestational Period - Yngrid Mickaelli Oliveira dos Santos; Igor Santana-Melo; Amanda Larissa Dias Pacheco; Milenna Maria Jatoba Hasten Reiter; Maisa de Araújo Costa; Keyla Silva Nobre Pires; Fernanda Maria Araújo de Souza; Jucilene Freitas-Santos; Mayara Rodrigues Barbosa; Jeferson Santana Ursulino; Marvin Paulo Lins; Rayssa Gabriely Duarte Torres; et al. (Molecular Neurobiology, 2025)

Differences in insulin resistance biomarkers, but not on serum zinc concentration, among individuals with different SLC30A8 genotypes: analysis of the São Paulo population-based study (2015 ISA-Nutrition) - Graziela Biude Silva Duarte; Cristiane Cominetti; Flavia Mori Sarti; Regina Mara Fisberg; Marcelo Macedo Rogero (Journal of Trace Elements in Medicine and Biology, 2025)

Evaluation of the toxic and genotoxic effects of exposure of Drosophila melanogaster to the glutathione-capped AgIn5Se8@ZnS nanocrystals - Antônio Marcos de Oliveira dos Santos; Danilo Gustavo Rodrigues Silva; Maria Gislaine Pereira; Adrielle Rodrigues Costa; Claudia Rohde; Camila Caroline Lopes Arruda; Antônia Eliene Duarte; Lizandra Ferraz da Silva; Denilson Vasconcelos Freitas; Marcelo Navarro; Maríndia Deprá; Daniela Maria do Amaral Ferraz Navarro; et al. (Chemosphere, 2025)

Multiblock NIR and MIR spectralprint through AComDim to evaluate the effects of growing site, harvest season, and clone on yerba mate leaves composition - Natalia Saudade de Aguiar; Gustavo Galo Marcheafave; Elis Daiane Pauli; Manoela Mendes Duarte; Ieda Spacino Scarminio; Roy Edward Bruns; Romà Tauler; Marcelo Lazzarotto; Ivar Wendling (Food Chemistry, 2025)

Lionfish on the Plate: Measures to Control the Species Invasion Result in Human Health Risks - Juliana de Souza-Araujo; Julia Vianna de Pinho; Caroline V. Feitosa; Oscar S. Duarte; Marcelo O. Soares; Rachel Ann Hauser-Davis; Tommaso Giarrizzo (Exposure and Health, 2025)

New records on autogenic behavior among populations of Ornithodoros fonsecai (Labruna and Venzal, 2009) (Ixodida: Argasidae) from northeastern Brazil - Ana Carolina Castro-Santiago; Leidiane Lima-Duarte; Jaqueline Valeria Camargo; Simone Michaela Simons; Ricardo Bassini-Silva; Ana Cláudia Calchi; Glauber Meneses Barboza de Oliveira; Maurício Cláudio Horta; Sebastián Muñoz-Leal; Marcelo Bahia Labruna; Marcos Rogério André; Rosangela Zacarias Machado; et al. (Veterinary Research Communications, 2025)

Enhancing orofacial pain relief: α-phellandrene complexed with hydroxypropyl-β-cyclodextrin mitigates orofacial nociception in rodents - Brennda Gonzaga Machado; Fabíolla Rocha Santos Passos; Ângelo Roberto Antoniolli; Erik W. Menezes Pereira; Tiffany Karoline Barroso Santos; Brenda Souza Monteiro; Pollyana de Souza Siqueira Lima; Saulo Santos Matos; Marcelo Cavalcante Duarte; Adriano Antunes de Souza Araújo; Jackson Roberto Guedes da Silva Almeida; Raimundo Gonçalves Oliveira Júnior; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Optimizing soil texture spatial prediction in the Brazilian Cerrado: Insights from random forest and spectral data - Marcelo Henrique Procópio Pelegrino; Luiz Roberto Guimarães Guilherme; Geraldo de Oliveira Lima; Raul Poppiel; Kabindra Adhikari; José Melo Demattê; Nilton Curi; Michele Duarte de Menezes (Geoderma Regional, 2025)

Confounding factors in the isotopic analysis of herbivore fecal samples - Isabela Pivetta Trentini; Marcelo Magioli; Francisco Grotta-Neto; Pedro Henrique de Faria Peres; Katia Maria P M B Ferraz; Marcelo Zacharias Moreira; Márcio Leite de Oliveira; José Maurício Barbanti Duarte (European Journal of Wildlife Research, 2025)

The small-scale fisheries sector in a developing country: assessing SWOT and recommendations for sustainability in Namibe (Angola) - Pinto Leonidio Hanamulamba; Tierry Val de Medeiros; Igor Hister Lourenço; Marcelo Rodrigues dos Anjos; Luis Felipe de Almeida Duarte (Fisheries Science, 2025)

Mite fauna (Acari: Erythraeidae and Otopheidomenidae) associated with hawkmoths (Lepidoptera: Sphingidae) in northeastern Brazil - Talitha Rochanne Alves Abreu da Costa; Maria Fernanda Santos Lima; Imeuda Peixoto Furtado; Marcelo Duarte (Experimental and Applied Acarology, 2025)

Botulinum toxin A dampened inflammatory response in BV-2 microglial cells - Mario Brito da Silva Filho; Gabriela Aniceto; Patrícia Maria Fernandes; Iara Gonçalves Aquino; Gustavo Duarte Mendes; Marcelo Henrique Napimoga; Juliana Trindade Clemente-Napimoga; Henrique Ballassini Abdalla (Toxicon, 2024)

Selenium biomarkers and miR‐7‐5p in overweight/obese women - Higor Paiva de Mendonça Alves; Graziela Biude Silva Duarte; Adriano Carlos de Souza Junior; Leonam da Silva Pereira Batista; Marcelo Macedo Rogero; Fernando Barbosa Jr; Silvia Maria Franciscato Cozzolino; Raquel Costa Silva Dantas-Komatsu; Karina Zaira Silva Marinho Costa; Bruna Zavarize Reis (Journal of Trace Elements in Medicine and Biology, 2024)

Neural networks in evaluating the post-harvest quality of strawberries fertilized with calcium and/or leaf silicon - Giulia Nayara Duarte; Hanna Elisia Araújo de Barros; Caio Vinicius Lima Natarelli; Jandeilson Pereira dos Santos; Lissa Izabel Ferreira de Andrade; Marcelo Henrique Avelar Mendes; Natalie Galhardo Ribeiro; Ana Beatriz Silva Araújo; Paulo César Ossani; Elisângela Elena Nunes Carvalho; Luciane Vilela Resende (Food and Humanity, 2024)

Were Dry Forests widespread in the Pleistocene and what is their fate under climate change? A modelling approach using a specialist plant - Mário Sérgio Duarte Branco; Paulo Weslem Portal Gomes; Laymara Xavier-Sampaio; José Luis Passos Cordeiro; Luciana dos Santos Dias de Oliveira; Eimear Nic Lughadha; Marcelo Freire Moro (Flora, 2024)

Eplingiella fruticosa leaf essential oil complexed with β-cyclodextrin exerts a neuroprotective effect in an Alzheimer’s disease animal model induced by Streptozotocin - Vanessa Alexandre-Silva; Beatriz Soares-Silva; Gabrielle Christine Pereira; Ana Claúdia Custódio-Silva; Patrícia Santos Carvalhinho-Lopes; Luciana Oliveira Taliano; Rafael Herling Lambertucci; Marcelo Duarte Cavalcante; Adriano Antunes de Souza Araújo; Lucindo Quintans-Júnior; José Ronaldo dos Santos; Alessandra Mussi Ribeiro (Metabolic Brain Disease, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Brazilian mangrove sediments as a source of biosurfactant-producing yeast Pichia pseudolambica for bioremediation - Júlio Ricardo Macedo Silva; Vitória Petra de Oliveira Barros; Pâmela Santos Terceiro; Ítalo Nunes de Oliveira; Orlando Francisco da Silva Moura; Johnnatan Duarte de Freitas; Alessandre Carmo Crispim; Vânia Maria Maciel Melo; Fabiano Lopes Thompson; Marcelo Maraschin; Melissa Fontes Landell (Chemosphere, 2024)

Process optimization for the removal of sodium diclofenac from water using a green polymeric membrane - Camila Suliani Raota; Jocelei Duarte; Janaina da Silva Crespo; Camila Baldasso; Marcelo Giovanela (Journal of Environmental Chemical Engineering, 2024)

How do non-deposit sites influence the performance of machine learning-based gold prospectivity mapping? A study case in the Pitangui Greenstone Belt, Brazil - Brener Otávio Luiz Ribeiro; Danilo Barbuena; Gustavo Henrique Coelho de Melo; João Gabriel Motta; Eduardo Duarte Marques; Marcelo de Souza Marinho (Journal of Geochemical Exploration, 2024)

Biosurfactants production by marine yeasts isolated from zoanthids and characterization of an emulsifier produced by Yarrowia lipolytica LMS 24B - Vitória Petra de Oliveira Barros; Júlio Ricardo Macedo Silva; Vânia Maria Maciel Melo; Pâmela Santos Terceiro; Italo Nunes de Oliveira; Johnnatan Duarte de Freitas; Orlando Francisco da Silva Moura; João Xavier de Araújo-Júnior; Erica Erlanny da Silva Rodrigues; Marcelo Maraschin; Fabiano Lopes Thompson; Melissa Fontes Landell (Chemosphere, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Enterobacteria in anaerobic digestion of dairy cattle wastewater: Assessing virulence and resistance for one health security - Kássia Vidal Menezes; Carlos Eduardo de Souza Duarte; Myleny Goularte Moreira; Talita de Jesus Cattem Moreno; Vitor José da Silva Pereira; João Gilberto Meza Ucella-Filho; Marcelo Henrique Otenio; Mariana Drummond Costa Ignacchiti; Juliana Alves Resende (Water Research, 2024)

Understanding ethical products: Definitions and attributes to consider throughout the product lifecycle - Taís Bisognin Garlet; Janine Fleith de Medeiros; José Luis Duarte Ribeiro; Marcelo Gattermann Perin (Sustainable Production and Consumption, 2024)

Nowcast flood predictions in the Amazon watershed based on the remotely sensed rainfall product PDIRnow and artificial neural networks - Herval Alves Ramos Filho; Eduardo Morgan Uliana; Uilson Ricardo Venâncio Aires; Ibraim Fantin da Cruz; Luana Lisboa; Demetrius David da Silva; Marcelo Ribeiro Viola; Victor Braga Rodrigues Duarte (Environmental Monitoring and Assessment, 2024)

Mineralogical fingerprint and human health risk from potentially toxic elements of Fe mining tailings from the Fundão dam - Danilo de Lima Camêlo; Luiz Aníbal da Silva Filho; David Lukas de Arruda; Luan Mauri Cyrino; Gilberto Fonseca Barroso; Marcelo Metri Corrêa; Paulo Jorge Sanches Barbeira; Danniel Brandão Mendes; Vânya Marcia Duarte Pasa; Demetrius Profeti (Science of The Total Environment, 2024)

The antiproliferative activity of Varronia dardani (Taroda) J.S. Mill. roots against human melanoma cells and the isolation of a new hydroanthraquinone - Carlos Arthur Gouveia Veloso; César Augusto Gonçalves Dantas; Raimundo Gonçalves de Oliveira Júnior; Vicente Carlos de Oliveira Costa; Luiz Antonio Miranda de Souza Duarte-Filho; José Iranildo Miranda de Melo; Pierre Edouard Bodet; Josean Fechine Tavares; Marcelo Sobral da Silva; Laurent Picot (Phytochemistry Letters, 2024)

Increased aridity and chronic anthropogenic disturbance reduce litter productivity in a Caatinga dry forest - Daniele Duarte Kulka; Bruno K.C. Filgueiras; Alice Batista dos Santos; Anna Carolina Pereira Locatelli; Jamerson Domingos de França; Silvia Rafaela Machado Lins; Marcelo Tabarelli (Forest Ecology and Management, 2024)

Population biology of the endangered land crab Johngarthia lagostoma (H. Milne Edwards, 1837) in the Trindade Island, Brazil: Identifying crucial areas for future conservation strategies - Marcio Camargo Araujo João; Rafael Campos Duarte; Andrea Santarosa Freire; Nicholas Kriegler; Marcelo Antonio Amaro Pinheiro (Marine Ecology, 2024)
The life history of insular gecarcinid crabs is divided into a marine larval and an adult phase, adapted to the terrestrial environment. As adults, individuals migrate seasonally to locations near the sea, engaging in reproductive behaviors. Therefore, identifying breeding and recruitment areas is crucial for the conservation of insular gecarcinids, especially for those endangered, such as Johngarthia lagostoma (H. Milne Edwards, 1837). We used sex ratio and sexual dimorphism analyses (body and cheliped size) as well as records of juveniles and adults to describe the population structure of J. lagostoma in the Trindade Island, Brazil. During the reproductive period, several population parameters were compared among sites with different altitudes, comprising two beaches (Andradas and Tartarugas) and two hills (Príncipe, 136 m; and Desejado, 612 m). Overall, males predominated in the population and invested more in body and cheliped growth than females. However, at Andradas Beach, it was observed a similar frequency of adult males and females as well as a small difference in the body size between the sexes. In comparison, the smallest crabs were found at Príncipe Hill. The analyzed population presented a predominance of adults, especially at Andradas Beach (93.1%). Compared to the other sites sampled, Príncipe Hill showed the highest abundance of juveniles (males: 22.2%; females: 40.8%). Thus, Andradas Beach was considered a reproductive site, while Príncipe Hill had the highest density of juveniles, which makes them priority areas for the conservation of J. lagostoma in Trindade Island.

Hemoperitoneum after a Bothrops snakebite: Case report - Adriana Baqueiro Abad Ribeiro; Marcelo Larami Santoro; Marcelo Ribeiro Duarte; Cristiana Cruz Virgulino; Gerson Sobrinho Salvador de Oliveira; Francisco Oscar de Siqueira França (Toxicon, 2024)

Digital mapping of soil classes in Southeast Brazil: environmental covariate selection, accuracy, and uncertainty - Maria Eduarda Carvalho Monteiro; Fábio Pomar Avalos; Marcelo Henrique Procópio Pelegrino; Raísa Brito Vilela; Fausto Weimar Acerbi Júnior; Inácio Thomaz Bueno; Nan Li; Sérgio Henrique Godinho Silva; Elvio Giasson; Nilton Curi; Michele Duarte de Menezes (Journal of South American Earth Sciences, 2023)

Intraspecific color diversity and camouflage associated with ontogeny in an insular land crab - Marcio C. A. João; Rafael C. Duarte; Andrea S. Freire; Marcelo A. A. Pinheiro (Behavioral Ecology and Sociobiology, 2023)

Soil parent material spatial modeling at high resolution from proximal sensing and machine learning: A pilot study - Luiza Maria Pereira Pierangeli; Sérgio Henrique Godinho Silva; Anita Fernanda dos Santos Teixeira; Marcelo Mancini; Renata Andrade; Michele Duarte de Menezes; Mona-Liza C. Sirbescu; João José Marques; David C. Weindorf; Nilton Curi (Journal of South American Earth Sciences, 2023)

SEM-imaging-based mapping of monofractal and multifractal patterns of the Piper krukoffii Yunck leaf surface architecture - Glenda Quaresma Ramos; Ituany da Costa Melo; Robert S. Matos; Erveton P. Pinto; Marcelo A. Pires; Edgar Aparecido Sanches; Henrique Duarte da Fonseca Filho (Flora, 2023)

Lessons from the invasion front: Integration of research and management of the lionfish invasion in Brazil - Marcelo O. Soares; Pedro H.C. Pereira; Caroline V. Feitosa; Rodrigo Maggioni; Rafael S. Rocha; Luis Ernesto Arruda Bezerra; Oscar S. Duarte; Sandra V. Paiva; Eurico Noleto-Filho; Maiara Queiroz M. Silva; Mayra Csapo-Thomaz; Tatiane M. Garcia; et al. (Journal of Environmental Management, 2023)

Geochemical mapping by stream sediments of the NW portion of Quadrilátero Ferrífero, Brazil: Application of the exploratory data analysis (EDA) and a proposal for generation of new gold targets in Pitangui gold district - Eduardo Duarte Marques; Cassiano Costa Castro; Renato de Assis Barros; Júlio César Lombello; Marcelo de Souza Marinho; Joanna Chaves S. Araújo; Everton A.M. Santos (Journal of Geochemical Exploration, 2023)

Efficient microbial cellulose/Fe3O4 nanocomposite for photocatalytic degradation by advanced oxidation process of textile dyes - Rayany Magali da Rocha Santana; Daniella Carla Napoleão; Joan Manuel Rodriguez-Diaz; Rayssa Kelen de Mendonça Gomes; Marina Gomes Silva; Victor Marcelo Estolano de Lima; Antônio Acacio de Melo Neto; Glória Maria Vinhas; Marta Maria Menezes Bezerra Duarte (Chemosphere, 2023)

Detailed characterization of plinthic soils in Southern Mali, Sub-Saharan Africa, as a secure basis for specific soil management and food security - Tales Emanuel Duarte Santos; Felipe Haenel Gomes; Marcelo Mancini; Gabriel Nuto Nóbrega; Junior Cesar Avanzi; João José Marques; Valdomiro Severino de Souza Júnior; Alberto Vasconcellos Inda; Marx Leandro Naves Silva; Nilton Curi (CATENA, 2023)

Morphological variation of the epiphyses in some Ambulycini hawkmoths (Lepidoptera, Sphingidae, Smerinthinae) - Georgette Paola Ancajima; Marcelo Duarte (Zoologischer Anzeiger, 2023)

Mechanical wounding impacts the growth versus defense balance in tomato (Solanum lycopersicum) - Ana Flavia Aparecida Cunha; Pedro Henrique Duarte Rodrigues; Ana Clara Anghinoni; Vinicius Juliani de Paiva; Daniel Gonçalves da Silva Pinheiro; Marcelo Lattarulo Campos (Plant Science, 2023)

Glimpsing the chemical composition and the potential of Myrtaceae plant extracts against the food spoilage fungus Thielaviopsis ethacetica - Jorge Andrés Duarte; Gabrielle Alves Ribeiro da Silva; Francisco Paiva Machado; Diogo Folly; Evelyn Peñaloza; Rafael Garrett; Marcelo Guerra Santos; José Aires Ventura; Guilherme Freimann Wermelinger; Bruno Kaufmann Robbs; Leandro Rocha; Sorele Batista Fiaux (Food Control, 2023)

Norfloxacin prophylaxis effect on multidrug resistance in patients with cirrhosis and bacterial infections - Sebastián Marciano; Maria N. Gutierrez-Acevedo; Sabrina Barbero; Lorena del C. Notari; Marina Agozino; Jose L. Fernandez; Maria M. Anders; Nadia Grigera; Florencia Antinucci; Orlando F. Orozco Ganem; Maria D. Murga; Daniela Perez; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Interactions between invaders: facilitation of boring bivalves leads to reduced adhesive strength of sun corals - Damián Mizrahi; Rafael C. Duarte; Marcelo V. Kitahara; Augusto A. V. Flores (Coral Reefs, 2023)

Experimental insecticide applications change tomato pollinator assemblages and do not increase fruit production - Edivani Villaron Franceschinelli; Joicy Martins Morais; Leonardo Lima Bergamini; Igor Madureira de Assis; Luiz Gustavo Fraga Rosa Paniago; Melissa Duarte Tavares Cardoso; Carlos de Melo e Silva Neto; Vanessa Gonzaga Marcelo; Pedro Vale de Azevedo Brito; Luísa Gigante Carvalheiro (Agriculture, Ecosystems & Environment, 2023)

Saponite-inspired Materials as Remediation Technologies for Water Treatment: an Overview - Dihêgo Henrique L. Damacena; Pollyana Trigueiro; Victor Hugo Monteiro; Luzia Maria C. Honorio; Thiago Marinho Duarte; Robson Cunha; Marcelo B. Furtini; Maria Gardennia Fonseca; Edson C da Silva-Filho; Josy A. Osajima (Environmental Processes, 2023)

Plasma Concentration of Essential and Toxic Trace Elements After Brazil Nut Intake: Results from a Randomized Controlled Trial - Graziela Biude Silva Duarte; Bruna Zavarize Reis; Marcelo Macedo Rogero; Fernando Barbosa; Cintia Cercato; Silvia Maria Franciscato Cozzolino (Biological Trace Element Research, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Simultaneous evaluation of benzotriazoles, benzothiazoles and benzenesulfonamides in water samples from the impacted urban Jacarepaguá Lagoon System (Rio de Janeiro, Brazil) by liquid chromatography coupled to electrospray tandem mass spectrometry - Soraya de Mendonça Ochs; Thallis Martins Souza; Rodrigo de Lima Sobrinho; Rodrigo B. de Oliveira; Marcelo Corrêa Bernardes; Annibal Duarte Pereira Netto (Science of The Total Environment, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Evaluation of urban pollution in a tropical lacustrine ecosystem by using n-alkanes and sterols as biomarkers - Rodrigo de Lima Sobrinho; Gabriel da Costa Peçanha; Thallis Martins de Souza; Luiz Carlos Cotovicz Junior; Luciana Oliveira Vidal; Annibal Duarte Pereira Netto; Marcelo Corrêa Bernardes (Environmental Pollution, 2023)

Niche modelling and comparative morphology untangle taxonomy of the Dysschema eurocilia clade (Lepidoptera: Erebidae) and reveal a relictual Pleistocene Arc distribution - Simeão DE Souza Moraes; Patrícia Eyng Gueratto; Jessie Pereira Dos Santos; Mateus Henrique Santos; André Victor Lucci Freitas; Marcelo Duarte (Systematics and Biodiversity, 2022)

Speciation process on Brazilian continental islands, with the description of a new insular lancehead of the genus Bothrops (Serpentes, Viperidae) - Fausto E. Barbo; William W. Booker; Marcelo R. Duarte; Betina Chaluppe; José A. Portes-Junior; Francisco L. Franco; Felipe G. Grazziotin (Systematics and Biodiversity, 2022)

In silico design and in vitro assessment of anti-Helicobacter pylori compounds as potential small-molecule arginase inhibitors - Ana Thereza Fiori-Duarte; João Paulo de Oliveira Guarnieri; Jessica Rodrigues Pereira de Oliveira Borlot; Marcelo Lancellotti; Ricardo Pereira Rodrigues; Rodrigo Rezende Kitagawa; Daniel Fábio Kawano (Molecular Diversity, 2022)

Lionfish on the loose: Pterois invade shallow habitats in the tropical southwestern Atlantic - Marcelo O. Soares; Caroline V. Feitosa; Tatiane M. Garcia; Kelly Ferreira Cottens; Bruno Vinicius; Sandra Vieira Paiva; Oscar de Sousa Duarte; Lívio Moreira Gurjão; Grasielle Dayse de Vasconcelos Silva; Rafaela Camargo Maia; Diego M. Previatto; Pedro B. M. Carneiro; et al. (Frontiers in Marine Science, 2022)
Lionfish ( Pterois spp.) evolved in the Indo-Pacific with predators and prey and invaded regions (e.g., the Caribbean Sea and Mediterranean) where no such balance yet exists. In 2020, four lionfish were recorded on mesophotic reefs of the Amazon offshore Coast and Fernando de Noronha Archipelago. However, until now, there were no records of invasive lionfish in Brazilian nearshore waters or even such a high number of individuals. In this article, we report the continuing invasion process along the Brazilian Province by multiple sightings (72) of lionfish from March to May 2022 in estuaries, seagrass beds, and artificial and natural reefs across 240 km of the Brazilian coast. These are the first records of lionfish in coastal northeast Brazil and the shallowest records (1–16 m) from South Atlantic tropical waters. The largest simultaneous records of lionfish in breakwaters, fishing weirs, and marambaias (artificial reefs used as fishing grounds) on the Brazilian Northeastern coast indicate that these man-made structures are suitable habitats for this species. Most of the lionfish (58%) were recorded in artificial reefs and fishing weirs. Moreover, the detection of invasions in marginal reefs, estuaries, and two marine protected areas characterized by moderately turbid water and high sedimentation rates highlights the adaptability of the lionfish, making it extremely difficult for divers and fishers to capture them. We call for an urgent management plan considering that the invaded tropical region hosts a high level of endemism, and rare and/or cryptic taxa, which increases the risk of impacts since these are primary lionfish prey.

Seasonal effect on biomarker responses in sentinel species: innovation in mangrove conservation status assessment - Caroline Araújo de Souza; Luis Felipe de Almeida Duarte; Flávia Pinheiro Zanotto; Priscila Ortega; Renata Guimarães Moreira; Marcelo Antonio Amaro Pinheiro (Environmental Monitoring and Assessment, 2022)

Sunlight Irradiated Pyrite-Fenton System for Advanced Oxidative Treatment of Textile Dyes Mixture - Rayany Magali da Rocha Santana; Daniella Carla Napoleão; Sérgio Gonzaga dos Santos Júnior; Rayssa Kelen de Mendonça Gomes; Alex Leandro Andrade de Lucena; Graziele Elisandra do Nascimento; Victor Marcelo Estolano de Lima; Antônio Acacio de Melo Neto; Giovanna Machado; Ana Maria Mendonça de Albuquerque Melo; Marta Maria Menezes Bezerra Duarte (Water, Air, & Soil Pollution, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

Phytochemical screening and cardiovascular effects of the ethanol extract of Erythroxylum passerinum mart - Bianca Leite Santos; Allan John de Oliveira; Izabelly Vieira Santos; Marcelo Cavalcante Duarte; Patrícia Santos Cunha; Danillo Menezes dos Santos; Eric Aian Pereira da Silva; Lucindo José Quintans Júnior; Márcio Roberto Viana dos Santos (Natural Product Research, 2022)

FIRST REPORT OF GENUS Cryptosporidium IN CERVIDS SPECIES: Mazama americana, Mazama nana AND Blastocerus dichotomus - Weslen Fabricio Pires Teixeira; Márcio Leite de Oliveira; Pedro Henrique de Faria Peres; Bruno César Miranda Oliveira; Walter Bertequini Nagata; Dielson da Silva Vieira; Anassilton Moreira de Andrade Junior; Elis Domingos Ferrari; José Maurício Barbanti Duarte; Marcelo Vasconcelos Meireles; Welber Daniel Zanetti Lopes; Katia Denise Saraiva Bresciani (Veterinary Research Communications, 2022)

Self-shading effect in the growth, photosynthesis and anatomy of Typha domingensis Pers. - Ana Lívia Martins Scarpa; Yasmini da Cunha Cruz; Marcio Paulo Pereira; Evaristo Mauro de Castro; Marcelo Polo; Vinícius Politi Duarte; Fabricio José Pereira (Brazilian Journal of Botany, 2021)

Reactive Phenanthrene Derivatives as Markers of Amino Groups in Fluorescence Microscopy of Surface Modified Micro-Zeolite L - Izadora Fonseca Reis; Larissa Schumekel Foltran; Milena Helmer Lauer; Marcelo Henrique Gehlen; Roberta Lopes Drekener; Carlos Roque Duarte Correia (Journal of Fluorescence, 2021)

New source of alleles for resistance to black spot and phoma spot in papaya (Carica papaya L.) - Adriana Azevedo Vimercati Pirovani; Helaine Christine Cancela Ramos; Renato Santa-Catarina; Tathianne Pastana de Sousa Poltronieri; Julio Cesar Fiorio Vettorazzi; Pedro Henrique Araújo Diniz Santos; Josefa Grasiela Silva Santana; Rafaela Pereira Duarte; Marcelo Vivas; Messias Gonzaga Pereira (Euphytica, 2021)

Inferring the mating system in the burrowing shrimp Lepidophthalmus bocourti (Decapoda, Axiidea, Callichiridae) from the social structure and sexual dimorphism - Patricio Hernáez; Erick Villegas-Castro; Marcio Camargo Araujo João; Rafael Campos Duarte; Marcelo M. Rivadeneira (Behavioral Ecology and Sociobiology, 2021)

In vitro and in silico studies of 8(17),12E,14-labdatrien-18-oic acid in airways smooth muscle relaxation: new molecular insights about its mechanism of action - Edilson B. Alencar Filho; Luciano A. A. Ribeiro; Thiego G. C. Carvalho; Fabrício S. Silva; Luiz Antonio M. S. Duarte-Filho; Euzébio G. Barbosa; Pedro M. N. Menezes; Josean F. Tavares; Marcelo S. da Silva; Bagnólia A. Silva (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Feeding Habit and Lifestyle Influence the Baseline Micronuclei Frequency of Crab Species in Pristine Mangroves - Marcelo Antonio Amaro Pinheiro; Nicholas Kriegler; Caroline Araújo de Souza; Luis Felipe de Almeida Duarte (Wetlands, 2021)

Reduced cutaneous inflammation associated with antioxidant action after topical application of the aqueous extract of Annona muricata leaves - Luana M. Cercato; Jéssica M. D. Araújo; Alan S. Oliveira; Allan J. O. Melo; Bruno S. Lima; Edmilson W. P. dos Santos; Agenor G. dos S. Neto; Ricardo L. C. de Albuquerque-Júnior; Marcelo C. Duarte; Adriano A. S. Araujo; Ana Mara O. Silva; Renata Grespan; et al. (Inflammopharmacology, 2021)

Pectobacterium carotovorum subsp. actinidiae associated with canker on pear trees in Brazil - Leonardo Araujo; Yuliet Franco Cardoza; Valmir Duarte; Marcelo Gravina de Moraes (European Journal of Plant Pathology, 2021)

Modeling anaerobic digestion metabolic pathways for antibiotic-contaminated wastewater treatment - Rafael Frederico Fonseca; Guilherme Henrique Duarte de Oliveira; Marcelo Zaiat (Biodegradation, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Effects of turmeric extract supplementation on inflammation and muscle damage after a half-marathon race: a randomized, double-blind, placebo-controlled trial - Flávia Rasmussen Faria; Aline Corado Gomes; Alisson Antunes; Kênnia Rocha Rezende; Gustavo Duarte Pimentel; Camila Lemos Pinto Oliveira; Barbara Moura Antunes; Fabio Santos Lira; Marcelo Saldanha Aoki; João Felipe Mota (European Journal of Applied Physiology, 2020)

Effectiveness of silicon sources for in vitro development of gerbera - Diogo Pedrosa Corrêa da Silva; Patricia Duarte de Oliveira Paiva; Raírys Cravo Herrera; Jorge Marcelo Padovani Porto; Michele Valquíria dos Reis; Renato Paiva (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Heat Waves Are a Major Threat to Turbid Coral Reefs in Brazil - Gustavo A. S. Duarte; Helena D. M. Villela; Matheus Deocleciano; Denise Silva; Adam Barno; Pedro M. Cardoso; Caren L. S. Vilela; Phillipe Rosado; Camila S. M. A. Messias; Maria Alejandra Chacon; Erika P. Santoro; Daniele B. Olmedo; et al. (Frontiers in Marine Science, 2020)

Evaluation of the cytotoxicity on breast cancer cell of extracts and compounds isolated from Hyptis pectinata (L.) poit - Fernanda R. Santana; Liany Luna-Dulcey; Víctor U. Antunes; Claudio F. Tormena; Marcia R. Cominetti; Marcelo C. Duarte; James A. da Silva (Natural Product Research, 2020)

Application of multivariate analysis on naphthalene adsorption in aqueous solutions - Lucas Mironuk Frescura; Bryan Brummelhaus de Menezes; Rafael Duarte; Marcelo Barcellos da Rosa (Environmental Science and Pollution Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Population biology and breeding cycle of the burrowing shrimp Callichirus seilacheri (Decapoda, Callianassidae) from the eastern tropical Pacific - Patricio Hernáez; Erick Villegas-Castro; Rafael Campos Duarte; Marcelo Antonio Amaro Pinheiro (Invertebrate Reproduction & Development, 2019)

Combination Therapy with Sulfasalazine and Valproic Acid Promotes Human Glioblastoma Cell Death Through Imbalance of the Intracellular Oxidative Response - Carlos Gustavo Garcia; Suzana Assad Kahn; Luiz Henrique Medeiros Geraldo; Igor Romano; Ivan Domith; Deborah Christinne Lima e Silva; Fernando dos Santos Assunção; Marcos José Ferreira; Camila Cabral Portugal; Jorge Marcondes de Souza; Luciana Ferreira Romão; Annibal Duarte Pereira Netto; et al. (Molecular Neurobiology, 2018)

Biofertilizer Replace Urea as a Source of Nitrogen for Sugarcane Production - Henrique Vieira de Mendonça; Carlos Eugênio Martins; Wadson Sebastião Duarte da Rocha; Cristiano Amancio Vieira Borges; Jean Pierre Henry Balbaud Ometto; Marcelo Henrique Otenio (Water, Air, & Soil Pollution, 2018)

Methionine and/or Methionine Sulfoxide Alter Ectoenzymes Activities in Lymphocytes and Inflammatory Parameters in Serum from Young Rats: Acute and Chronic Effects - Mayara Sandrielly Pereira Soares; Marcelo Zanusso Costa; Tatiane Morgana da Silva; Marta Gazal; Carlus Augustu Tavares do Couto; Gabriela Nogueira Debom; Rodrigo Rodrigues; Juliana Hofstätter Azambuja; Emerson André Casali; Cesar Eduardo Jacintho Moritz; Marta Frescura Duarte; Elizandra Braganhol; et al. (Cell Biochemistry and Biophysics, 2018)

Long-term stability of the hawkmoth fauna (Lepidoptera, Sphingidae) in a protected area of Brazilian Atlantic Rain Forest - Pedro I. Chiquetto-Machado; Felipe W. Amorim; Marcelo Duarte (Journal of Insect Conservation, 2018)

Relevance of genetic relationship in GWAS and genomic prediction - Helcio Duarte Pereira; José Marcelo Soriano Viana; Andréa Carla Bastos Andrade; Fabyano Fonseca e Silva; Geísa Pinheiro Paes (Journal of Applied Genetics, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Extreme sexual dimorphism and polymorphism in two species of the tiger moth genus Dysschema (Lepidoptera: Erebidae): association between males and females, sexual mimicry and melanism revealed by integrative taxonomy - SimeÃo De Souza Moraes; Lucas Waldvogel Cardoso; Karina Lucas Silva-brandÃo; Marcelo Duarte (Systematics and Biodiversity, 2017)

Association between inflammation processes, DNA damage, and exposure to environmental pollutants - Anelise Barth; Natália Brucker; Angela M. Moro; Sabrina Nascimento; Gabriela Goethel; Caroline Souto; Rafael Fracasso; Elisa Sauer; Louise Altknecht; Bárbara da Costa; Marta Duarte; Camila B. Menezes; et al. (Environmental Science and Pollution Research, 2017)

Energy and protein requirements of young Holstein calves in tropical condition - João Paulo Pacheco Rodrigues; Jessika Carolina Moutinho Lima; Marcelo Messias Duarte Castro; Sebastião de Campos Valadares Filho; Mariana Magalhães Campos; Mário Luiz Chizzotti; Marcos Inácio Marcondes (Tropical Animal Health and Production, 2016)

Nutritional and productive performance of dairy cows fed corn silage or sugarcane silage with or without additives - Felipe Leite de Andrade; João Paulo Pacheco Rodrigues; Edenio Detmann; Sebastião de Campos Valadares Filho; Marcelo Messias Duarte Castro; Aline Souza Trece; Tadeu Eder Silva; Vivian Fischer; Kirsten Weiss; Marcos Inácio Marcondes (Tropical Animal Health and Production, 2016)

Rhizopus arrhizus and Fusarium solani Concomitant Infection in an Immunocompromised Host - João N. de Almeida Júnior; Karim Y. Ibrahim; Gilda M. B. Del Negro; Evandro D. Bezerra; Amaro N. Duarte Neto; Marjorie V. Batista; Rinaldo F. Siciliano; Mauro C. Giudice; Adriana L. Motta; Flávia Rossi; Ligia C. Pierrotti; Maristela P. Freire; et al. (Mycopathologia, 2016)

A breakthrough on Amanita phalloides poisoning: an effective antidotal effect by polymyxin B - Juliana Garcia; Vera Marisa Costa; Alexandra T. P. Carvalho; Ricardo Silvestre; José Alberto Duarte; Daniel F. A. R. Dourado; Marcelo D. Arbo; Teresa Baltazar; Ricardo Jorge Dinis-Oliveira; Paula Baptista; Maria de Lourdes Bastos; Félix Carvalho (Archives of Toxicology, 2015)

The antiatherogenic effect of bixin in hypercholesterolemic rabbits is associated to the improvement of lipid profile and to its antioxidant and anti-inflammatory effects - Sabrina Somacal; Cassieli G. Figueiredo; Andréia Quatrin; Amanda R. Ruviaro; Lisiane Conte; Paula R. Augusti; Miguel Roehrs; Ione T. Denardin; Jocieli Kasten; Marcelo L. da Veiga; Marta M. F. Duarte; Tatiana Emanuelli (Molecular and Cellular Biochemistry, 2015)

Phylogeny and recombination analysis of Brazilian yellow passion fruit isolates of Cowpea aphid-borne mosaic virus: origin and relationship with hosts - Leilane K. Rodrigues; Leonardo A. Silva; Renata M. Garcêz; Alexandre L. R. Chaves; Ligia M. L. Duarte; José S. Giampani; Addolorata Colariccio; Ricardo Harakava; Marcelo Eiras (Australasian Plant Pathology, 2015)

Action of growing degree days on the morphogenesis and physiological responses of calla lily - Marcelo Rodrigues; Patrícia Duarte de Oliveira Paiva; João Paulo Rodrigues Alves Delfino Barbosa; Thaís de Oliveira Fontes Mansur (Acta Physiologiae Plantarum, 2014)

Determination of Monoaromatic Hydrocarbons (BTEX) in Surface Waters from a Brazilian Subtropical Hydrographic Basin - Andreia Neves Fernandes; Cindy Duarte Gouveia; Marco Tadeu Grassi; Janaina da Silva Crespo; Marcelo Giovanela (Bulletin of Environmental Contamination and Toxicology, 2014)

Mitochondrial Cumulative Damage Induced by Mitoxantrone: Late Onset Cardiac Energetic Impairment - Luciana Grazziotin Rossato; Vera Marisa Costa; Eliane Dallegrave; Marcelo Arbo; Renata Silva; Rita Ferreira; Francisco Amado; Ricardo Jorge Dinis-Oliveira; José Alberto Duarte; Maria de Lourdes Bastos; Carlos Palmeira; Fernando Remião (Cardiovascular Toxicology, 2014)

Erratum to: NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina R. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina C. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

Anxiogenic-like profile of Wistar adult rats based on the pilocarpine model: an animal model for trait anxiety? - Filipe S. Duarte; Marcelo Duzzioni; Alexandre A. Hoeller; Nayana M. Silva; Andy L. Ern; Tetsade C. Piermartiri; Carla I. Tasca; Elaine C. Gavioli; Tadeu Lemos; Antonio P. Carobrez; Thereza C. M. De Lima (Psychopharmacology, 2013)

Patterns of population differentiation in annual killifishes from the Paraná–Uruguay–La Plata Basin: the role of vicariance and dispersal - Graciela García; Verónica Gutiérrez; Julia Vergara; Pablo Calviño; Alejandro Duarte; Marcelo Loureiro (Journal of Biogeography, 2012)
Aim To elucidate the role of vicariance versus dispersal at the microevolutionary scale in annual killifish populations belonging to the Austrolebias bellottii species complex (Rivulidae). Within this complex, A. bellottii and A. apaii have low vagility and occur widely within the study area, making them excellent models for testing biogeographic hypotheses of differentiation. Location South America, in the Paraná–Uruguay–La Plata river basin. Methods Molecular data and morphometric analyses were used to reconstruct the phylogeographic history and morphological variation of 24 populations of two taxa of the A. bellottii species complex. Phylogenetic analyses using maximum likelihood (ML) and Bayesian inference (BI) model‐based methods, estimates of clade divergence times implemented in beast , non‐metric multidimensional scaling, analysis of molecular variance results, and morphological analyses elucidated the role of vicariance versus dispersal hypotheses in population differentiation in the aforementioned river basin. Results In the A. bellottii species complex from the Paraná–Uruguay–La Plata river basin, past allopatric fragmentation from vicariance events seems to be the most plausible scenario for diversification since the Late Miocene and more recently since the Plio‐Pleistocene. The Plio‐Pleistocene vicariance produced the differentiation of three major clades in A. bellottii populations. One clade from the eastern Uruguay River drainage was separated from another in western Uruguay and the Paraná–La Plata River drainages. A later vicariance event split populations to the south (lower Paraná–La Plata Basin) and north (middle Paraná) of the western Paraná River drainage. However, our results do not exclude the possibility of dispersal events among A. bellottii populations from both the Uruguay and Paraná river drainages, which could occur in these river basins during hypothesized connectivity cycles of the Late Pliocene and Pleistocene. Main conclusions Past allopatric fragmentation caused by different vicariance events seems to be the main driver of diversification in the A. bellottii species complex since the Plio‐Pleistocene. However, the current molecular data suggest that populations from both drainages of the Paraná–Uruguay rivers may have experienced cycles of connectivity during the Pleistocene, perhaps including multiple vicariance or dispersal events from populations located in the western lower Uruguay River drainage, which encompassed climatic and geological changes in the Paraná–Uruguay–La Plata Basin.

Molecular characterization of a miraculin-like gene differentially expressed during coffee development and coffee leaf miner infestation - Jorge Maurício Costa Mondego; Melina Pasini Duarte; Eduardo Kiyota; Leandro Martínez; Sandra Rodrigues de Camargo; Fernanda P. De Caroli; Beatriz Santos Capela Alves; Sandra Maria Carmello Guerreiro; Maria Luiza Vilela Oliva; Oliveiro Guerreiro-Filho; Marcelo Menossi (Planta, 2011)

Short- and long-term anxiogenic effects induced by a single injection of subconvulsant doses of pilocarpine in rats: investigation of the putative role of hippocampal pathways - Filipe Silveira Duarte; Elaine Cristina Gavioli; Marcelo Duzzioni; Alexandre Ademar Hoeller; Newton Sabino Canteras; Thereza Christina Monteiro De Lima (Psychopharmacology, 2010)

Anticonvulsant and anxiolytic-like effects of compounds isolated from Polygala sabulosa (Polygalaceae) in rodents: in vitro and in vivo interactions with benzodiazepine binding sites - Filipe Silveira Duarte; Mariel Marder; Alexandre Ademar Hoeller; Marcelo Duzzioni; Beatriz Garcia Mendes; Moacir Geraldo Pizzolatti; Thereza Christina Monteiro De Lima (Psychopharmacology, 2008)

Inheritance of Aluminum Tolerance and its Effects on Grain Yield and Grain Quality in Oats (Avena Sativa L.) - Itamar Cristiano Nava; Carla Andréa Delatorre; Ismael T. de Lima Duarte; Marcelo Teixeira Pacheco; Luiz Carlos Federizzi (Euphytica, 2006)

Life cycle and host specificity of Amblyomma triste (Acari: Ixodidae) under laboratory conditions - Marcelo B. Labruna; Eric Y.M. Fugisaki; Adriano Pinter; José Maurício B. Duarte; Matias J.P. Szabó (Experimental and Applied Acarology, 2003)

Exotic snakes in São Paulo City, southeastern Brazil: why xenophobia? - André Eterovic; Marcelo Ribeiro Duarte (Biodiversity and Conservation, 2002)